The value of an additional scrotal suture during orchidopexy. Issue 1 (February 2021) - Hirner, L.; Rübben, I.; Lax, H.; Hirner, C.; Panic, A.; Darr, C.; Krafft, U.; Hadaschik, B.; Niedworok, C.; Rehme, C.
Summary: Introduction: Undescended testes present in 3–5% of male infants at birth. Orchidopexy is indicated to improve fertility and reduce the risk of testicular tumors. Guidelines recommend orchidopexy as early as six months of age, treatment should be finished within the age of 18 months. So far, no unequivocal proof demonstrated the superiority of one of the different surgical techniques. Objective: To evaluate the value of an additional scrotal suture between the tunica albuginea and the dartos fascia during orchidopexy in an outpatient setting. It is yet unclear, whether the suture influences the incidence of secondary cryptorchidism or recurrence. Study design: This is a retrospective cohort study. Between 2010 and 2018 two experienced surgeons performed 561 inguinal orchidopexy-procedures in an open technique (375 boys). In group 1 (2010–2014) they managed 234 IOP (156 boys) without an additional scrotal suture. Since 2014, in group 2 an additional suture has been performed in 327 IOP (219 boys). Statistically, we compared both groups over a period of consecutive 4 years after the model of a life table analysis (Logrank). Results: The numbers of boys with complete follow-up were 118 of 156 in group 1 and 154 of 219 in group 2, demonstrating 7 (5.9%) and 7 (4.5%) recurrences, respectively. There was no statistically significant difference in recurrences between group 1 and group 2 (Logrank-Test, p = 0.97). Orchidopexie failure was detected between 0.9 and 23.1 months after the IOP in group 1 and between 3.2 and 17.7 months in group 2. Mean age in months at the operation in both groups was significantly higher than the recommended 6–18 months in the EAU/AUA-guidelines. Both groups showed similar rates of postoperative complications. Discussion: Orchidopexy is a safe procedure in an outpatient setting. So far there is no evidence that performing an additional scrotal suture decreases the operative failure rate in inguinal standard orchidopexy procedures. Summary Table 1 Testicular position and atrophy of the patients with follow up. Summary Table 1   Patients with Follow Up Group 1 N = 118 Group 2 N = 154 Relaps  no 111 147  yes 7 7 Position  Inguinal 7 7  scrotal 111 147 Testicle Atrophy  no 118 154  yes 0 0